2006
DOI: 10.1242/dev.02252
|View full text |Cite
|
Sign up to set email alerts
|

Foxf1andFoxf2control murine gut development by limiting mesenchymal Wnt signaling and promoting extracellular matrix production

Abstract: Development of the vertebrate gut is controlled by paracrine crosstalk between the endodermal epithelium and the associated splanchnic mesoderm. In the adult, the same types of signals control epithelial proliferation and survival, which account for the importance of the stroma in colon carcinoma progression. Here, we show that targeting murine Foxf1 and Foxf2, encoding forkhead transcription factors, has pleiotropic effects on intestinal paracrine signaling. Inactivation of both Foxf2 alleles, or one allele e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
228
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(247 citation statements)
references
References 45 publications
16
228
2
Order By: Relevance
“…What is more intriguing is the essential role of key regulators of VM development from flies to vertebrates. Mutations in FoxF TFs cause defects in gut muscle differentiation in both mice (Mahlapuu et al 2001a;Wang et al 2003;Ormestad et al 2004Ormestad et al , 2006 and Xenopus (Tseng et al 2004), similar to those observed in flies (Zaffran et al 2001). Likewise, BapX is required for the specification of subtypes of VM in mice (Lettice et al 1999) and flies (Azpiazu and Frasch 1993).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…What is more intriguing is the essential role of key regulators of VM development from flies to vertebrates. Mutations in FoxF TFs cause defects in gut muscle differentiation in both mice (Mahlapuu et al 2001a;Wang et al 2003;Ormestad et al 2004Ormestad et al , 2006 and Xenopus (Tseng et al 2004), similar to those observed in flies (Zaffran et al 2001). Likewise, BapX is required for the specification of subtypes of VM in mice (Lettice et al 1999) and flies (Azpiazu and Frasch 1993).…”
mentioning
confidence: 74%
“…As Foxf1 and Foxf2 are partially functionally redundant within the splanchnic mesoderm (Ormestad et al 2004(Ormestad et al , 2006, target gene expression is expected to be only moderately reduced in either single mutant. Double null mutants cannot be generated as compound heterozygotes die at birth (Ormestad et al 2006). Foxf1 −/− mutant embryos die between embryonic day 9.5 (E9.5) and E10.5 (Mahlapuu et al 2001b), while Foxf2 −/− mutants develop to term (Wang et al 2003).…”
Section: Conservation In the Foxf Regulatory Circuitry From Flies To mentioning
confidence: 99%
“…The transcription factors Foxf1 and Foxl1 have been identified as direct Hh target genes (40), and both genes are expressed in the fetal intestinal mesenchyme, in a similar pattern as Ptc1 (41,42). Targeted inactivation of Foxf1 or Foxl1 results in an abnormal intestinal architecture with irregularly shaped villi (7,8). It is possible that the villus-inducing role of Hh is mediated at least in part by Foxf1 and Foxl1.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, increased Wnt5a expression in the surrounding stroma activates the canonical Wnt pathway with stabilized b-catenin in epithelial cells leading to epithelial hyperproliferation and resistance to apoptosis. 70 Oncogene-induced hyperplasia (the efferent signal) triggers a stromal response initiating a vicious cycle of paracrine afferent signals leading to tumor invasion and loss of tissue integrity. A key question is to identify the efferent signals (cancer cellderived) that have an impact on myofibroblast attraction, differentiation, proliferation and production of proinvasive signals.…”
Section: Characterization and Origin Of A Myofibroblastmentioning
confidence: 99%